Association of triglyceride glucose index with diabetic retinopathy in middle-aged and elderly ambulatory type 2 diabetic patients - Yao, Qiong; Liu, Shang-quan (Frontiers in Endocrinology, 2025)
BackgroundDiabetic retinopathy (DR) is a major contributor to vision loss and blindness among working-age adults worldwide. While the relationship between the triglyceride glucose (TyG) index and DR in hospitalized patients has been demonstrated, research on the correlation between the triglyceride glucose (TyG) index and DR in ambulatory type 2 diabetes mellitus (T2DM) patients is still relatively limited.MethodsA cohort of 398 middle-aged and elderly T2DM patients who underwent outpatient physical examinations at the First People’s Hospital of Hefei City between 2012 and 2017 were included in this study. They were categorized into either the nondiabetic retinopathy group (296 cases in the NDR group) or the diabetic retinopathy group (102 cases in the DR group) based on the results of dilated fundus examinations. One-way logistic regression and LR backward multifactorial logistic regression analyses were utilized to identify the risk factors associated with the development of diabetic retinopathy in T2DM patients. Furthermore, the predictive value of the TyG index for diabetic retinopathy in middle-aged and elderly ambulatory T2DM patients was evaluated through stratified regression to adjust for other factors, along with receiver operating characteristic (ROC) curve analysis.ResultsMultivariate logistic regression analysis indicated that the TyG index was identified as an independent risk factor for diabetic retinopathy (DR) in middle-aged and elderly patients with type 2 diabetes mellitus (T2DM) (P < 0.05). The receiver operating characteristic (ROC) curve analysis revealed that the area under the curve (AUC) was 0.585 [95% CI (0.524, 0.646)] (P = 0.011), with an optimal cut-off value of 9.115, corresponding to a sensitivity of 82.4% and specificity of 36.1%.ConclusionThe TyG index serves as an independent risk factor for diabetic retinopathy (DR) in middle-aged and elderly ambulatory type 2 diabetes mellitus (T2DM) patients, and it is recommended that this index be used as a reference index in the comprehensive assessment of DR.